FY2019 Dominican Republic Country Opinion Survey Report - World Bank Group (World Bank, Washington, DC, 2019)
The country opinion survey in Dominican Republic assists the World Bank Group (WBG) in gaining a better understanding of how stakeholders in Dominican Republic perceive the WBG. It provides the WBG with systematic feedback from national and local governments, multilateral and bilateral agencies, media, academia, the private sector, and civil society in Dominican Republic on: (1) their views regarding the general environment in Dominican Republic; (2) their overall attitudes toward the WBG in Dominican Republic; (3) overall impressions of the WBG’s effectiveness and results, knowledge work and activities, and communication and information sharing in Dominican Republic; and (4) their perceptions of the WBG’s future role in Dominican Republic.